A Neolithic population model based on new radiocarbon dates from mining, funerary and population scaled activity in the Saint-Gond Marshes region of North East France. (10th June 2021) - Edinborough, Kevan; Martineau, Rémi; Dufraisse, Alexa; Shennan, Stephen; Imbeaux, Marie; Dumontet, Anthony; Schauer, Peter; Cook, Gordon
Abstract: We present and model new radiocarbon data for the Neolithic marshes of Marais de Saint-Gond Marne in France. We then provide the first radiocarbon-based synthesis of human activity in this region. The earliest flint mine pits dug in France were dated to between 7518 and 7356 cal BC (95% probability) in the Mesolithic period. A Neolithic sequence of activity has been reconstructed in detail for the mine and hypogeums in the Vert-la-Gravelle "La Crayère" site. Using summed probability distribution frequencies with new radiocarbon results from flint mines, hypogeum-burials and settlements, we show the peak of regional population is consistent with the advent of the hypogeum construction during the Néolithique récent/Néolithique final between 3650 and 2900 cal BC (95% probability).